Potential Treat-to-Target Approach for Methamphetamine Use Disorder: A Pilot Study of Adenosine 2A Receptor Antagonist With Positron Emission Tomography - Okita, Kyoji; Matsumoto, Toshihiko; Funada, Daisuke; Murakami, Maki; Kato, Koichi; Shigemoto, Yoko; Sato, Noriko; Matsuda, Hiroshi (Frontiers in Pharmacology, 2022)
Introduction The use of amphetamine-type stimulants such as methamphetamine is a global public health issue. One important neurochemical mechanism of Methamphetamine Use Disorder may be altered dopaminergic neurotransmission. For instance, individuals with substance use disorders have been consistently observed to exhibit lower D2-type receptor availability (quantified as binding potential; BPND) using positron emission tomography (PET). Further, methamphetamine use is known to induce chronic neuroinflammation through multiple physiological pathways. Upregulation of D2-type receptor density and/or attenuation of neuroinflammation may therefore provide a therapeutic effect for this disorder. In vitro studies have shown that blockage of adenosine 2A (A2A) receptors may prevent D2-receptor downregulation and neuroinflammation-related brain damage. As such, A2A receptor antagonists may have therapeutic effects in individuals with methamphetamine use disorders. However, no study has currently examined this hypothesis yet. Methods and analysis This within-subject design trial aims to evaluate the effect of the A2A receptor antagonist istradefylline mainly on both dopamine D2-type receptor availability in the human brain, and secondarily on neuroinflammation in the whole brain. It is hypothesized that istradefylline will increase striatal D2-type BPND and attenuate neuroinflammation. Twenty participants with methamphetamine use disorder, aged 20–65, will be recruited to undergo [11C]raclopride PET (for every participant) and [11C]DAA1106 PET (if applicable) once before and once after administration of either 40mg/day istradefylline for two weeks. Neuropsychological measurements will be administered on the same days of the PET scans. Ethics and dissemination The study protocol was approved by the Certified Review Boards (CRB) of National Center of Neurology and Psychiatry (CR20-002) and prospectively registered with the Japan Registry of Clinical Trials (jRCTs031200330; https://jrct.niph.go.jp/latest-detail/jRCTs031200330). The findings of this study will be disseminated through peer reviewed scientific journals and conferences.